Predictors of Bullying among Athletes in the Romanian Context - Florin Nichifor; Andrei-Lucian Marian; Silviu-Mihail Tiţă (MDPI AG, 2023)
The purpose of this study was to examine the explanatory power of a predictive model of bully/perpetrator behaviour in Romanian athletes, consisting of negative pre-competitive emotions (anxiety, sadness, and anger), perception of male gender normativity, and relationships with coaches and teammates. Additionally, we aimed to explore the mediation effect of bully-victim behaviour on the relationship between athletes' connections with their coaches and bully/perpetrator behaviour. The current research involved a nonexperimental, cross-sectional design exploring the presence of bully/perpetrator behaviour in Romanian male and female athletes. The quantitative methodology was used to collect and analyse the data obtained. Researchers translated, adapted and pretested the questionnaire set to the Romanian cultural background (SEQ, MAMS, CART-Q, In-group Ties Scale, BSQ) before distributing it to 448 participants. 58.7% were male participants, and 41.3% were female participants. The mean age was 21.15 (SDage = 2.37, range = 18-32). The research was conducted in the first half of 2023. SPSS (V. 20) and Hayes's PROCESS tool were used to investigate the data. The findings demonstrated that in the case of Romanian male athletes, perception of male gender normativity, anger, and weaker connections with coaches are the most important psychological factors in predicting bully/perpetrator behaviour. In contrast, in the case of Romanian female athletes, only weaker connections with coaches and perception of male gender normativity play an essential role in explaining bully/perpetrator behaviour. Additionally, the study demonstrated that bully-victim behaviour mediates the relationship between athletes' weaker connections with their coaches and bully/perpetrator behaviour. Athletes' weaker connections with their coaches lead to experiencing a high level of bully/perpetrator behaviour by stressing bully-victim behaviour, which also contributes to achieving a high level of bully/perpetrator behaviour.